Proposição de um modelo de referência para gestão da qualidade na cadeia de produção de leite e de derivados. - Scalco, Andréa Rossi (Universidade Federal de São Carlos, 2004)
The competitivity and the survival of Brazilian dairy, and consequently the dairy production chain, are conditioned to an improvement of products quality and to competitive production costs. The costumer health can be put in risk due to consumption of products in which the quality characteristics are altered, leading the costumer to not purchase the product again, injuring the company image and its survival. The costs, wastes and flaws are above the acceptable standards.According to the diagnosis made by SCALCO (1999), it was observed that there are significant flaws in the quality management system in the major part of dairy industries studied, compromising the final product quality and generating losses in the production process. Some examples of these flaws are: no preventive technical support for the milk suppliers, strong dependence from the inspection and control of the raw material and the final product, use of labor force not well qualified and distribution control process without quality control. The found flaws are not limited just to the industrial segment; they can be felt all over the production of the milk chain and similar product. Due to the fact of the perishable characteristic of these products, the condition of hygiene and refrigeration should be kept trough the chain. By this, it is justified the elaboration of a model to manage the quality trough this chain; considering its specifications in the search for an effective instrument in the quality coordination. The model essentially consists in a system to coordinate information; identification of the problems and elaboration of improvement plans managed by a coordinating agent. The elaboration of the model is established on bibliographical revision about system and techniques of quality management; agro food chain coordination; field research for the acquaintance of the problems and practices of management and coordination of the quality all over the segment of the milk chain and similar; secondary data about the sector and its quality management. The work presents an illustration of the model, as well as an evaluation of it by the sector specialists. This evaluation has shown that this model can be considered original, clear, adequate to the dairy production chain reality, adaptable to its particularities, it contains necessary elements to coordinate the quality and contribute for the improvement and preservation of the product quality, also reducing costs and losses in its part of the production chain.
Keywords: Gestão da qualidade total; Controle de qualidade; Leite produção; Coordenação; CIENCIAS EXATAS E DA TERRA::FISICA